2010
DOI: 10.1246/cl.2010.564
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Heterochirality of a 1:2 Metal/Ph-pybox Complex Ion by ESIMS

Abstract: The heterochirality of a 1:2 metal/Ph-pybox complex ion was encyclopedically evaluated by ESIMS using pseudoracemic (R,R)-and (S,S)-Ph-pybox pair, which were unlabeled/labeled by deuterium atoms, respectively. The heterochiral complex was predominantly formed in all investigated 1:2 metal/Ph-pybox complex ions.The bis(oxazolinyl)pyridine (Sub-pybox, Sub = substituent) family of tridentate ligands were first developed by Nishiyama and co-workers for enantioselective organometallic catalysis, 1 and have also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…For comparison, a freshly prepared 1:1:1 mixture of ( R )‐ L Ph , ( S )‐ L Ph and iron(II) salt does contain both diastereomers. That is consistent with a previous report that {Fe(( R )‐ L Ph )[( S )‐ L Ph ]} 2+ exists as a single isomer with a diastereomeric excess of 0.95, as measured by mass spectrometry …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For comparison, a freshly prepared 1:1:1 mixture of ( R )‐ L Ph , ( S )‐ L Ph and iron(II) salt does contain both diastereomers. That is consistent with a previous report that {Fe(( R )‐ L Ph )[( S )‐ L Ph ]} 2+ exists as a single isomer with a diastereomeric excess of 0.95, as measured by mass spectrometry …”
Section: Resultssupporting
confidence: 93%
“…The optical purity of ( R )‐ versus ( RS )‐[M( L Ph ) 2 ] 2+ derivatives in solution has been investigated before, but ( R )‐ versus ( RS )‐[M( L i Pr ) 2 ] 2+ has not. It was unexpected that ( RS )‐ 4 undergoes significant racemization through ligand redistribution in solution (Figure ), whereas ( RS )‐ 3 does not (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous 1 H NMR studies have shown that (RS)-[M(L Ph ) 2 ] 2+ (M = Fe, Co or Zn) are stable in solution, and don't undergo racemisation by ligand redistribution [6,10,12]. This was also confirmed in the gas phase, by mass spectrometry [9]. Comparison of the 1 H NMR spectra of (RS)-1 and (RS)-3 with their homochiral congeners confirms that conclusion (Figure 4 and Supporting Information) Figure . There is no evidence for partial decoordination of L Ph in the spectra of the zinc complexes, as was observed for the triflate salt of (R)-1 under some conditions [12].…”
Section: Resultsmentioning
confidence: 55%
“…<Insert Scheme 1 here> That study was possible, because heterochiral [Fe((R)-L Ph )((S)-L Ph )][ClO 4 ] 2 is stable in solution, and does not undergo detectable racemisation through ligand redistribution [9]. The same is true for salts of the analogous complexes [M((R)-L Ph )((S)-L Ph )] 2+ (M = Co [10,11], Zn [12], Cu [13] or another metal ion [9]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation